SnO2 nanorod: An efficient non-noble-metal electrocatalyst for non-enzymatic H2O2 sensing. (29th March 2019) - Zhou, Fuling; Wang, Zao; Xu, Bo; Xia, Li; Xiong, Xiaoli; Sun, Xuping
Abstract: Developing non-noble-metal electrocatalyst for non-enzymatic H2 O2 sensing is highly attractive. In this work, we describe the development of SnO2 nanorod grown on carbon cloth (SnO2 /CC) as an efficient electrocatalyst for H2 O2 reduction in neutral solution. The SnO2 /CC electrode reveals superior electrochemical performance as a non-enzymatic electrochemical H2 O2 sensor, with an ultra-high sensitivity of 24 840 μ A mM −1 cm -2, a low detection limit of 9.94 nM at S/N = 3, a linear range from 0.10 μ M to 1.0 mM, and satisfactory reproducibility and stability at −0.40 V.